2014
DOI: 10.4161/cc.29104
|View full text |Cite
|
Sign up to set email alerts
|

The Down syndrome-related protein kinase DYRK1A phosphorylates p27Kip1and Cyclin D1 and induces cell cycle exit and neuronal differentiation

Abstract: A fundamental question in neurobiology is how the balance between proliferation and differentiation of neuronal precursors is maintained to ensure that the proper number of brain neurons is generated. Substantial evidence implicates DYRK1A (dual specificity tyrosine-phosphorylation-regulated kinase 1A) as a candidate gene responsible for altered neuronal development and brain abnormalities in Down syndrome. Recent findings support the hypothesis that DYRK1A is involved in cell cycle control. Nonetheless, how D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
123
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(130 citation statements)
references
References 80 publications
(154 reference statements)
5
123
1
1
Order By: Relevance
“…Cyclin D1 expression is upregulated by mitogenic signaling through the Ras-signaling pathway involving Ras/Raf/mitogen-activated protein [21]. Cyclin D1 levels are also posttranslationally regulated by its degradation through the following ubiquitin-proteasome pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin D1 expression is upregulated by mitogenic signaling through the Ras-signaling pathway involving Ras/Raf/mitogen-activated protein [21]. Cyclin D1 levels are also posttranslationally regulated by its degradation through the following ubiquitin-proteasome pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Our data have shown that loss of Hap1 can lead to enhanced interaction between Dcaf7 and DYRK1A, resulting in an increase in DYRK1A. It has been reported that increased DYRK1A can affect cell-cycle regulation and neuronal differentiation by reducing cyclin D1 and the cyclindependent kinase inhibitor p21 (49,50), two important proteins that promote neuronal differentiation (50)(51)(52)(53)(54). Thus, we isolated hypothalamic tissues from WT and Hap1-KO postnatal pups and performed Western blotting with anti-cyclin D1 and anti-p21.…”
Section: Hap1 Stabilizes the Protein Level Of Dcaf7 By Inhibiting Itsmentioning
confidence: 82%
“…18,19,21,44,45 The reduced brain size may be partially explained by the dual role of DYRK1A in inhibiting the proliferation of neuronal progenitors via suppression of NOTCH signaling and Cyclin D1 while also promoting neurogenesis by stabilizing the cyclindependent kinase inhibitor p27 (KIP1) . 46,47 In addition, DYRK1A interacts with the microtubule and actin cytoskeletal networks to regulate neurite outgrowth and synaptogenesis. [48][49][50] Through these mechanisms, haploinsuffciency of DYRK1A presumably leads to augmented neuronal precursor proliferation and apoptosis, decreased neurogenesis and abnormal neuritogenesis.…”
Section: Resultsmentioning
confidence: 99%